EVALUATION OF COATING PERFORMANCE FOR OFFSHORE STRUCTURES IN A HARSH ENVIRONMENT - MOHD JAMIL, HASIFI HAZIM (2018)
Offshore structures exposed to harsh environment require optimum protection through effective coating system. The objectives of this study is to evaluate the coating performances under harsh environment. In order to evaluate the coating performance of the coating system for offshore structure, the main experiment that have been done in order to stimulate the harsh environment is ageing test based on the standard. The testing consist of UV and condensation exposure, salt spray exposure and low temperature exposure. Validation of the coatings performance have been assess by pull off test, corrosion from scribe line, degree of blistering, degree of rusting and degree of chalking. The results for the pull off test demonstrate the little different of the value of pressure before and after the ageing test. Corrosion creep from the scribe line give a positive value that meet the minimum requirement of good coating system. Assessment of degree of blistering, rusting and chalking also shown that the coatings are in good condition without any sign of degradation. The outcome of this project would lead to the development of more effective coating system for offshore structures.